Relevansi Sumber Belajar Ketahanan Nasional Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan Dengan Indikator Pencapaian Kompetensi Siswa (Studi Di Sma Negeri 1 Surakarta, Jawa Tengah) - WIJIANTO WIJIANTO (Jurnal Ketahanan Nasional, 2019)
ABSTRACTThis study aims to determine: 1) the availability of national resilience learning resources for Civic Education subjects; 2) relevance of learning resources for national resilience in Civic Education subjects with indicators of student competency achievement; and 3) the obstacles experienced by teachers in the use of national resilience learning resources for Civic Education subjects.The study uses a qualitative approach that is strengthened by quantitative data. Data collection using interviews, observation, study documents, and questionnaires. Data validity testing uses data triangulation and method triangulation. Data analysis uses an interactive analysis model.Conclusions of the results of the study: 1) The availability of national resilience learning resources for PPKn subjects is quite adequate because there are available Student Books, Student Worksheet, and websites as a source of material for threats to the Republic of Indonesia. 2) Material to Be Wary of Threats to the Republic of Indonesia on learning resources for national resilience in PPKn subjects, especially Student Books, Student Worksheet, and the website does not meet the indicators of student competency achievement because the material only presents civic knowledge and civic disposition, while civic skills have not been fully presented because they only fulfill intellectual skills while participatory skills have not yet been fulfilled. 3) The obstacle of teachers in the use of national resilience learning resources for PPKn subjects for Student Books and Student Worksheet, which is there is material which is wrong and the extent of the material is lacking. The website is constrained by wifi signals and some contain invalid information.ABSTRAKPenelitian ini bertujuan untuk mengetahui: 1) ketersediaan sumber belajar ketahanan nasional mata pelajaran PPKn; 2) relevansi sumber belajar ketahanan nasional mata pelajaran PPKn dengan indikator pencapaian kompetensi siswa; dan 3) kendala yang dialami guru dalam pemanfaatan sumber belajar ketahanan nasional mata pelajaran PPKn.Penelitian menggunakan pendekatan kualitatif yang diperkuat data kuantitatif. Pengumpulan data menggunakan wawancara, observasi, studi dokumen, dan angket. Pengujian validitas data menggunakan triangulasi data dan triangulasi metode. Analisis data menggunakan model analisis interaktif.Kesimpulan hasil penelitian: 1) Ketersediaan sumber belajar ketahanan nasional mata pelajaran PPKn cukup memadai karena tersedia Buku Siswa, LKS, dan website sebagai sumber materi ancaman terhadap NKRI. 2) Materi Mewaspadai Ancaman terhadap NKRI pada sumber belajar ketahanan nasional mata pelajaran PPKn, khususnya Buku Siswa, LKS, dan website belum memenuhi indikator pencapaian kompetensi siswa karena materi hanya menyajikan civic knowledge dan civic disposition, sementara civic skill belum sepenuhnya disajikan karena baru memenuhi intellectual skills sedangkan participatory skills belum terpenuhi. 3) Kendala guru dalam pemanfaatan sumber belajar ketahanan nasional mata pelajaran PPKn untuk Buku Siswa dan LKS, yaitu terdapat materi yang keliru dan keluasan materinya kurang. Website terkendala sinyal wifi dan beberapa memuat informasi tidak valid.